Social capital and the extent of its contribution to enhancing the management of excellence: An applied study at Azadi Hospital / Duhok - Rashid, Ahmed Ibrahim; Hussein Almallah, Israa Tareq (Journal of Economics and Administrative Sciences, 2020)
The study aimed to reveal the role of social capital represented by its dimensions (structural, relational, and cognitive) in strengthening the management of excellence in Azadi Hospital / Duhok. In order to reach the goal of the study, the study variables were highlighted in theory through framing concepts and literary contributions for researchers in this field, In the field, the questionnaire was used as a basic tool to collect data from the individuals in the research sample who were represented by officials and individuals working from administrators and technicians, as (120) forms were distributed to the respondents, and (110) were retrieved from them in a way that is valid for analysis. Several statistical methods have been used in dealing with data and testing study hypotheses, including central tendency measures, correlation coefficient, and the regression line equation, A set of conclusions was reached the most important of which was the existence of the relationship and the moral impact of social capital in all its dimensions in the distinction management in the researched hospital and all the effects were good, which explains to us that there is tangible interest by the hospital examined with social capital, which reflected positively on the process of excellence and management Its activities, The study is out with several proposals, the most prominent of which is to support the dimensions of social capital in the researched organization by spreading the culture of cooperation and supporting social relations and clarifying its role in promoting excellence in the performance of activities and increasing their effectiveness as well as The possibility of benefiting from the strengths of the researched hospital in relation to social capital, which had a clear impact on managing excellence.